A Conceptualization of The Sme Digitalization Model To Support The "SME-Go Digital" Program in Indonesia - Broto Legowo, Mercurius; Indiarto, Budi; Prayitno, Deden (Indonesian Journal of Business and Entrepreneurship, 2022)
Nowadays, many business people and academic researchers are paying attention to improving digitalization in business and innovation for business models, especially in the case of SMEs. Many SMEs have not implemented digitalization then, they never think about the business model as an issue that underlies the conceptualization of the MSME digitization model in this study. This research aims to provide a conceptualization of the SME digitalization model to assist Indonesia's "SME-Go Digital" program. In this study, a qualitative approach was applied using descriptive methods. The development of a conceptual framework based on Grounded Theory and Perception Analysis from the results of the SME survey was used to conceptualize the SME digitalization model. The results of this study present a conceptualization of the SME digitization model used to support the Indonesian government's digitization program (“SMEs Go Digital”). This study concludes that the SME digitization model had developed using a conceptual framework based on the description of grounded theory. Furthermore, this study emphasizes the influence of dynamic capabilities on the digitization of SMEs, which impacts the development of Business Model Innovations. The Indonesian government's "SME-Go Digital" program will be partially supported by contributions from this research. Keywords: conceptualization, government program, model, SMEs digitalization